Online Peer-Tutoring for Programming Languages Based on Programming Ability and Teaching Skill - Yu-Chen Kuo; Ching-Bang Yao; Zhe-Yu Wu (Applied Sciences, 2022)
Web-based cooperative learning could enhance students’ learning motivation; however, learning activities in this process are rather confusing because of the lack of structured learning strategies, resulting in unfavorable learning achievements. With the peer tutoring learning environment to encourage students’ mutual learning and development, an online peer-tutoring platform for programming languages with peer mentoring is established herein for one-to-one peer tutoring activities. With students with higher learning ability as tutors and those with lower learning ability as tutees, tutors can provide online peer tutoring for programming languages via demonstrations and flowcharts to discuss the effects of using different teaching methods for learning activities on the learning achievement of tutees. Based on these teaching methods for peer learning, 52 undergraduates were divided into experimental groups A and B; each group was further divided into peer mentoring group and non-peer mentoring group based on the ability levels. The results show that learning activities with the online peer-tutoring platform for programming languages could assist both groups in enhancing their learning achievement and ensure positive attitudes toward programming languages. In the analyses, the peer mentoring group was preferable in peer tutoring for programming languages with demonstration, while the non-peer mentoring group did not appear significant.